Sea Surface Temperature Modulates Physiological and Immunological Condition of Octopus maya - Pascual, Cristina; Mascaro, Maite; Rodríguez-Canul, Rossanna; Gallardo, Pedro; Sánchez, Ariadna Arteaga; Rosas, Carlos; Cruz-López, Honorio (Frontiers in Physiology, 2019)
Octopus maya is a valuable endemic species of the Yucatán Peninsula (YP). This area can be divided into distinct regions depending on the presence of cold waters associated to upwelling events during spring and summer. This study was designed to determine if the physiological and immunological condition of O. maya show a relationship with variation of the sea surface temperature associated with the seasonal upwelling. A total of 117 organisms were collected from February to July in three fishing zones: Ria Lagartos located in the upwelling zone; Seybaplaya corresponding to the non-upwelling zone, and Sisal, the transitional zone. The organisms were examined in terms of physiological (total weight, the weight of the gonad and digestive gland, osmotic pressure, hemocyanin, protein, glucose and cholesterol concentrations in plasma), and immunological variables (total hemocyte count, hemagglutination, phenoloxidase system activity, total phenoloxidase plasma activity, and lysozyme activity). Multivariate one-way ANOVA showed overall significant differences between groups of octopus by month/ zone of capture, indicating that the physiological-immunological condition of O. maya is related to a temperature gradient. Wild octopuses captured at the upwelling zone and the transitional zone (Ría Lagartos and Sisal) in February, March, and April -with temperatures lower than 27 °C- were in better conditions: larger size, high concentrations of hemocyanin, and low activity of the phenoloxidase system. Octopuses captured in the warmer waters (28 to 30 °C) of the non-upwelling and transitional zones (Seybaplaya and Sisal) during June and July, could be reflecting the metabolic stress through immunological compensation mechanisms with higher activity of the phenoloxidase system, despite having a lower concentration of hemocytes, hemocyanin and proteins. Although the movement of individual O. maya along the YP throughout their life cycle has not yet been determined, direct development and benthic behavior could limit the mobility of the organisms in such a way that their physiological and immunological condition might reflect adaptation to the regional environment. This information could help understand the performance of octopuses in their distribution area, which sustains an important fishery.